Green synthesis of silver nanoparticles toward bio and medical applications: review study. (12th November 2018) - Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Ghasemi, Younes; Atapour, Amir; Amani, Ali Mohammad; Savar Dashtaki, Amir; Babapoor, Aziz; Arjmand, Omid
Abstract: Development of biologically inspired green synthesis of silver nanoparticles has attracted considerable worldwide attention in matter of medical science and disease treatment. Herein, the green synthesis of silver nanomaterials using organic green sources has been evaluated and discussed. These kinds of materials are widely used for treatment of antibiotic-resistant bacteria, cancer and etc due to their elegant properties compared with other chemical ways and drugs. Moreover, the outcome of green-based approaches were compared with chemical procedures and obtained data were examined via various analyses including UV-visible spectroscopy, scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX), transmission electron microscope (TEM), atomic force microscopy (AFM) and Fourier transforms infrared spectroscopy (FT-IR). In this study, variety of green methods were investigated to present a summary of recent achievements toward highlighting biocompatible nanoparticles, all of which can reduce the toxicity of nanoparticles, make them eco-friendly, reduce their side effects and decrease the production cost. The nature of these biological organisms also affect the structure, shape, size and morphology of synthesized nanoparticles.